Strategi Komunikasi Interpersonal Guru Bimbingan Konseling (Bk) Dalam Menangani Kenakalan Siswa Smk Negeri 8 Padang - Erika, Aulia Anggraini; Eriend, Dion (CV. ITTC INDONESIA, 2024)
Delinquency in students occurs because the condition of students is still unstable or in the process of searching for their identity. Apart from that, student delinquency can also be influenced by their environment, whether from family, friendship or community environment. With communication between teachers and students who have problems, they will experience their own satisfaction and experience catharsis (the release of the underlying problem with relief and understanding of the problem). But in helping to solve student problems, guidance and counseling teachers need various ways to find out the real problem, and to be able to provide students with an understanding that the student is having problems. Therefore, interpersonal communication strategies are really needed so that students who have problems can express something hidden beneath their self-awareness, beneath their abilities and beneath their feelings. Interpersonal communication strategies themselves have a big influence in changing bad student attitudes. Because face to face or individually, the teacher will know better the reasons why the student committed the act, making it easier for the teacher to find a solution or eliminate the student's bad behavior. Communication is an important aspect of human life, communication is divided into several types of communication, including: interpersonal communication and group communication. The research method used in this research is qualitative with a descriptive approach and uses Social Penetration theory. The results of this research explain the interpersonal communication strategies of guidance and counseling teachers in handling delinquency students at SMK Negeri 8 Padang with full empathy, understanding, openness and good relationships with students.